Tuberculosis screening in multiple sclerosis: effect of disease-modifying therapies and lymphopenia on the prevalence of indeterminate TB screening results in the clinical setting. Issue 3 (September 2019) - Baldassari, Laura E; Feng, Jenny; Macaron, Gabrielle; Planchon, Sarah M; Alshehri, Ebtesam; Moss, Brandon P; Ontaneda, Daniel; Willis, Mary A
Background: Tuberculosis screening is recommended in multiple sclerosis patients starting certain disease-modifying therapies. Disease-modifying therapies may affect interferon-gamma release assay results. Objective: To determine the effects of multiple sclerosis disease-modifying therapies on interferon-gamma release assay results. Methods: Indeterminate interferon-gamma release assay results among multiple sclerosis patients were compared across disease-modifying therapies by Fisher's exact test. Logistic regression evaluated the effects of lymphopenia on interferon-gamma release assay results. Results: A total of 1058 patients underwent interferon-gamma release assay: 2.0% (21) positive, 6.1% (65) indeterminate, with 59.4% (628) on disease-modifying therapies. Results were significantly different across disease-modifying therapies ( P = 0.002). Absolute lymphocyte count less than 0.5 k/μL had 9.39 times (95% confidence interval 5.2–17.0) increased odds of indeterminate interferon-gamma release assay results. Conclusions: Disease-modifying therapies affecting lymphocytes had a higher risk of indeterminate interferon-gamma release assay results.